Interannual Variability of Upwelling Along the Southern Java and Western Sumatra in 2003 - 2015 - Saut Hamonangan, Julianto
Upwelling is a process in which deep, water rises toward the surface, with a mass of water that rose to the surface has lower temperatures and higher salinity. Upwelling is significantly influenced by interactions with other natural phenomena, such ENSO (El Niño Southern Oscillation) and IOD (Indian Ocean Dipole). This study aims to determine the interannual variability of upwelling in the south Java and west Sumatra to the El Niño Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD). This research is using Aqua MODIS satellite image level 3 data for parameter sea surface temperature (SST) and chlorophyll-a, and surface wind data from the National Climate for Environmental Prediction (NCEP) in 2003 - 2015. The results show that when the IOD + accompanied El Niño - La Niña, period of upwelling 1-2 months longer than conditions generally, and reached the western part of Bengkulu. The lowest SST occurs when El Niño - IOD + (25,76 ° C), IOD + (25,86 ° C), and La Niña - IOD + (25,89 ° C), and the highest concentrations of chlorophyll-a occurs when El Niño - IOD + (23,42 mg / m3), IOD + (21,85 mg / m3), and La Niña - IOD + (8,44 mg / m3) . Strong upwelling occur when La Niña - IOD + and El Niño - IOD +, with SST anomaly of -1,51 ° C and -1,17 ° C, chlorophyll-a anomaly 2,6 mg / m3, with Ekman Pumping 5,54 x 10-6 m / s and 8,92 x 10-6 m / s. The weakest upwelling occurs in La Niña conditions - IOD -, with SPL anomaly of 1,51 ° C, chlorophyll-a anomaly -0,82 mg / m3, with Ekman Pumping 5.37 x 10-6 m / s. The results also showed that the IOD more influential in strengthening the upwelling than ENSO.